Ultrasound Imaging of Abdominal Wall Endometriosis: A Pictorial Review - Giulio Cocco; Andrea Delli Pizzi; Marco Scioscia; Vincenzo Ricci; Andrea Boccatonda; Matteo Candeloro; Marco Tana; Giuseppe Balconi; Marcello Romano; Cosima Schiavone (Diagnostics, 2021)
Endometriosis is a debilitating disease characterized by endometrial glands and stroma outside the endometrial cavity. Abdominal wall endometriosis (AWE) indicates the presence of ectopic endometrium between the peritoneum and the skin, including subcutaneous adipose tissue and muscle layers, often following obstetric and gynecological surgical procedures. AWE is a not infrequent gynecological surgical complication, due to the increasing number of cesarean sections worldwide. In this pictorial review, we discuss the importance of medical history and physical examination, including the main ultrasound features in the diagnosis of AWE.